Tracing COVID-19 Source of Infection Among Health Personnel in a Pediatric Hospital - de la Rosa-Zamboni, Daniela; Ortega-Riosvelasco, Fernando; González-García, Nadia; Gamiño-Arroyo, Ana Estela; Espinosa-González, Guillermo Alejandro; Valladares-Wagner, Juan Manuel; Saldívar-Flores, Araceli; Aguilar-Guzmán, Olivia; Sanchez-Pujol, Juan Carlos; López-Martínez, Briseida; Villa-Guillén, Mónica; Parra-Ortega, Israel; et al. (Frontiers in Pediatrics, 2022)
Health Personnel (HP) have been universally recognized as especially susceptible to COVID-19. In Mexico, our home country, HP have one of the highest death rates from the disease. From the beginning of the SARS-CoV-2 pandemic an office for initial attention for HP and a call center were established at a COVID-19 national reference pediatric hospital, aimed to early detection of COVID-19 cases and to stop local transmission. The detection and call center implementation and operation, and tracing methodology are described here. One thousand and forty two HP were evaluated, with 221 positive cases identified (7.7% of all HP currently working and 26% of the HP tested). Community contagion was most prevalent (46%), followed by other HP (27%), household (14%) and hospitalized patients (13%). Clusters and contact network analysis are discussed. This is one of the first reports that address the details of the implementation process of contact tracing in a pediatric hospital with the perspective of a hybrid hospital with COVID-19 and Non COVID-19 areas.